Implementation of Entrepreneurship Education to Foster University Students' Entrepreneurial Interest - Iyan (Darul Yasin Al Sys, 2026)
Although entrepreneurship education has received considerable scholarly attention, research examining how its learning processes are implemented to foster university students’ entrepreneurial interest remains limited. This study aims to analyze the implementation of entrepreneurship education in fostering students’ entrepreneurial interest and identify the factors that support or hinder this process. A qualitative approach with a library research design was employed. Data were obtained through a documentary review of scholarly articles, books, official reports, and other publications relevant to entrepreneurship education. The data were analyzed using content analysis involving data reduction, thematic categorization, data presentation, and conclusion drawing. The findings indicate that entrepreneurship education integrated with practical activities, such as business-plan development, business-idea presentations, and entrepreneurship exhibitions, enhances students’ business understanding, strengthens their self-confidence, and encourages them to initiate entrepreneurial ventures. Entrepreneurial interest is further supported by personal motivation, lecturer support, a conducive campus environment, and advances in digital technology. Conversely, limited experience, insufficient financial capital, and fear of failure remain major barriers. The study concludes that practice-oriented entrepreneurship education is essential for cultivating university students’ entrepreneurial interest and preparing independent, innovative graduates capable of creating employment opportunities. These findings contribute to the development of entrepreneurship education in higher education and provide a foundation for designing learning models that are more responsive to evolving business environments and digital transformation.